Precision medicine to prevent glaucoma-related blindness. Issue 3 (May 2019) - Moroi, Sayoko E.; Reed, David M.; Sanders, David S.; Almazroa, Ahmed; Kagemann, Lawrence; Shah, Neil; Shekhawat, Nakul; Richards, Julia E.
Abstract : Purpose of review: Approximately 10% of patients become blind despite using evidence-based guidelines developed from clinical trials and epidemiology studies. Our purpose is to review opportunities to decrease glaucoma-related blindness using the emerging principles of precision medicine. Recent findings: The current review focuses on three topics: first, candidate biomarkers for angle-based surgeries, second, head-mounted display (HMD) technology for vision and testing, and third, glaucoma risk alleles discovered by genome-wide association studies. First, in angle-based surgeries, tracers injected into the anterior chamber or Schlemm's canal have allowed visualization of aqueous veins. We describe an innovative use of optical coherence tomography angiography to visualize aqueous veins in a case with 6-year successful outcome following catheter-based trabeculotomy. Second, HMD technology can augment perceived vision and can be used for perimetry testing. Third, developing genetic risk scores that characterize patients who are at highest risk for blindness is a priority. Such biomarker risk scores will integrate genome-wide association study-based risk alleles for glaucoma along with well known demographic and clinical risk factors. Summary: As we gain more knowledge, precision medicine will enable clinicians to decrease glaucoma-related blindness by providing more timely interventions to those patients who are at highest risk for progression to blindness. Video abstract: http://links.lww.com/COOP/A29 . Abstract : Supplemental Digital Content is available in the text